Methods and stability tests associated with the sterile neutrino search using improved high-energy νμ event reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review D, 2024)
We provide supporting details for the search for a 3+1 sterile neutrino using data collected over 10.7 years at the IceCube Neutrino Observatory. The analysis uses atmospheric muon-flavored neutrinos from 0.5 to 100 TeV that traverse Earth to reach the IceCube detector and finds a best-fit point at sin2(2θ24)=0.16 and Δm412=3.5 eV2 with a goodness-of-fit p value of 12% and consistency with the null hypothesis of no oscillations to sterile neutrinos with a p value of 3.1%. Several improvements were made over past analyses, which are reviewed in this article, including upgrades to the reconstruction and the study of sources of systematic uncertainty. We provide details of the fit quality and discuss stability tests that split the data for separate samples, comparing results. We find that the fits are consistent between split datasets.
CRIS-Team Scopus Importer:2024-11-29